The economics of circular migration - Amelie F. Constant; Olga Nottmeyer; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2012)
Circular migration receives increasing attention due to its empirical relevance and as a policy concept to manage labor flows. This review discusses the advantages and disadvantages of circular movements for all parties. It studies the characteristics of circular movers worldwide and investigates the consequences of restrictive migration policies. Recent policy initiatives that aim to manage circular labor movement are also analyzed.
Keywords: J61; F22; F24; 330; geographic labor mobility; immigrant workers; international migration; remittances; Internationale Arbeitsmobilität; Rücküberweisung (Migranten); Rückwanderung; Saisonarbeitskräfte; Migrationspolitik; Kosten-Nutzen-Analyse; Welt